Corrigendum to: Is Tapping on Acupuncture Points an Active Ingredient in Emotional Freedom Techniques. Issue 8 (August 2020) - Church, Dawson; Stapleton, Peta; Kip, Kevin; Gallo, Fred
Abstract : Abstract: We published a meta-analysis of component trials of emotional freedom techniques (EFT) in this journal. EFT is an evidence-based method, validated in over 100 clinical trials, that uses fingertip tapping on acupressure points in conjunction with techniques from exposure and cognitive therapy. The meta-analysis examined six studies in which an active control, such as diaphragmatic breathing or sham acupoints, was used in place of tapping on actual acupoints. The purpose of the meta-analysis was to determine whether tapping was an inert or an active ingredient in EFTs observed treatment effects. Subsequent to publication, errors in the statistical analysis were identified, primarily incorrect standard deviation values, and our methodological approach was questioned by others. We therefore had the meta-analysis rerun by an independent senior statistician who compared pre- to follow-up results to determine the sustained effects of treatment. The cumulative fixed effects Hedge's g -value was found to be 0.73 (95% confidence interval = 0.42–1.04, p < 0.0001). The corresponding random effects Hedge's g -value is 0.74 (95% confidence interval = 0.34–1.13, p < 0.0001). We also reviewed and clarified our methodology. In conclusion, despite computational errors in our original publication, the present revised analysis supports the original conclusion that the acupressure component of the EFT protocol is an active ingredient that contributes to the method's favorable health effects. Abstract : Supplemental digital content is available in the text.